ANALISIS KEKUATAN DAN UMUR KELELAHAN SHAFT PROPELLER KAPAL DENGAN METODE KOMPUTASIONAL - Adiel Fadhlan Yazid (2022)
The planning of a ship requires a propulsion system that has a function as a propulsion system on the ship. In the propulsion system, there is one part, the shaft. In the process of the working shaft receives various forces and loads so that several aspects need to be considered, among others, the strength of the shaft and the material used. This study aims to find out the value of stress and fatigue age on the shaft of the landing craft tank (LCT) 1500 DWT made of stainless steel material 316 with variations of loading. The method used in this study is the finite element method, supplemented by the Structural Ansys application. The resulting value in software is von mises stress and the shortest cycle value of fatigue life. The results of the analysis obtained a 100% stress value of 195.24 MPa and 100% + 10% loading stress of 214.76 Mpa and then the value will be compared to the material permit stress of 202.54 MPa. For the fatigue life of the ship shaft loading 100% with a cycle of 3.2312x108 which is 17.46 years for an operational time of 300 days / year and 20.96 years for operations of 250 days/ year. Loading 100 %+ 10% with a cycle of 2.2868 x 108 is 12.36 years for an operational time of 300 days/ year and 14.83 years for 250 days / year operations.